EU‒Africa Relations: Migration Diplomacy Approach - Lyubov S. Bisson (Современная Европа)
The article offers a fresh insight into the relations between the European Union and Africa from “migration diplomacy” perspective which is being introduced in migration and international relations research in Russia. The author notes the explanatory and predictive potential of the “migration diplomacy” concept for considering the complex relations between states within different migration systems. The analysis of interactions and cooperation of the EU, as a receiving side, with the states of origin and transit of international migrants in Africa allowed to highlight the specifics of the EU approach. The latter consists in using various diplomatic means and formats to address the problem of illegal immigration and reducing the number of asylum seekers in the EU. The increasing dependence of the European Union on cooperation with third countries results in the use of migration as a tool of political pressure by partner states. Intra-continental migration processes are at the centre of the migration diplomacy of the African continent, including those related to freedom of movement. Despite the differences in the approaches of the parties, the potential for cooperation lies in the development of channels for legal labour migration.